Diagnostic Value of Physical Examination, Ultrasound, and Radiography Compared to Computed Tomography in the Evaluation of Nontraumatic Left Lower Quadrant Acute Abdominal Pain - Fakhroddin Kiani; Seyed Mostafa Meshkati Yazd; Fatemeh Zarimeidani; Rahem Rahmati; Nafiseh Shabani Mofrad; Mehdi Vafaei Nia; Reza Shahriarirad (Emergency Medicine International)
Conclusions: As a result of the highest sensitivity for PE and the highest accuracy for the US, we suggest considering PE as the primary investigation for identifying urgent conditions in patients with LLQ AAP and the US for an accurate diagnosis rather than PAR.